Design And Implementation of Tempe Sanan Industrial Village Brand Guidelines Edu-Futurism as A Strategic Step Towards Go International Branding - Prasetyo, Abdul Rahman; Wulandari, Dwi; Fajarianto, Otto; Aruna, Alby; Surya, Eka Putri; Marcelliantika, Adinda; Wijaya, Ginanjar Atma (Civiliza Publishing, 2024)
The design and implementation of Edu-Futurism brand guidelines for Kampung Industri Tempe Sanan represent a strategic step to enhance the image and competitiveness of local tempe products in the international market. This project involves a deep analysis of the cultural values and unique features of Sanan tempe, which are then translated into comprehensive brand guidelines. These guidelines encompass visual elements, brand messaging, and consistent communication strategies. The implementation results show increased brand awareness and global consumer interest in Sanan tempe products. This initiative is expected to support international branding efforts and strengthen Kampung Industri Tempe Sanan's position in the global market.